Concise Review: Mesenchymal Stem Cells Derived from Human Pluripotent Cells, an Unlimited and Quality-Controllable Source for Therapeutic Applications. (21st January 2019) - Jiang, Bin; Yan, Li; Wang, Xiaoyan; Li, Enqin; Murphy, Kyle; Vaccaro, Kyle; Li, Yingcui; Xu, Ren-He
Abstract : Despite the long discrepancy over their definition, heterogeneity, and functions, mesenchymal stem cells (MSCs) have proved to be a key player in tissue repair and homeostasis. Generally, somatic tissue-derived MSCs (st-MSCs) are subject to quality variations related to donated samples and biosafety concern for transmission of potential pathogens from the donors. In contrast, human pluripotent stem cells (hPSCs) are unlimited in supply, clear in the biological background, and convenient for quality control, genetic modification, and scale-up production. We, and others, have shown that hPSCs can differentiate in two dimensions or three dimensions to MSCs (ps-MSCs) via embryonic (mesoderm and neural crest) or extraembryonic (trophoblast) cell types under serum-containing or xeno-free and defined conditions. Compared to st-MSCs, ps-MSCs appear less mature, proliferate faster, express lower levels of inflammatory cytokines, and respond less to traditional protocols for st-MSC differentiation to other cell types, especially adipocytes. Nevertheless, ps-MSCs are capable of immune modulation and treatment of an increasing number of animal disease models via mitochondria transfer, paracrine, exosomes, and direct differentiation, and can be potentially used as a universal and endless therapy for clinical application. This review summarizes the progress on ps-MSCs and discusses perspectives and challenges for their potential translation to the clinic. Stem Cells 2019;37:572–581 : Abstract : Mesenchymal stem cells (MSCs) can be derived from somatic tissues (st-MSCs) such as human bone marrow or human pluripotent stem cell (ps-MSCs) including induced pluripotent stem cells derived from reprogrammed human somatic cells such as skin fibroblasts and embryonic stem cells derived from human blastocyst. Compared to st-MSCs, ps-MSCs possess remarkable advantages in cell supply, quality consistency, and pathogen control.